Generalized derivations of order $2$ on multilinear polynomials in prime rings - B. Prajapati; C. Gupta (Математичні Студії)
Let $R$ be a prime ring of characteristic different from $2$ with a right Martindale quotient ring $Q_r$ and an extended centroid $C$. Let $F$ be a non zero generalized derivation of $R$ and $S$ be the set of evaluations of a non-central valued multilinear polynomial $f(x_1,…,x_n)$ over $C$. Let $p,q\in R$ be such that